Immune-Inflammatory Parameters in COVID-19 Cases: A Systematic Review and Meta-Analysis - Feng, Xudong; Li, Shuangshuang; Sun, Qiang; Zhu, Jiaqi; Chen, Bo; Xiong, Maoming; Cao, Guodong (Frontiers in Medicine, 2020)
Background The recent outbreak of coronavirus disease 2019 (COVID-19) has been rapidly spreading on a global scale and posed great threat to human health. Acute respiratory distress syndrome, characterized by a rapid onset of generalized inflammation, is the leading cause of mortality of patients with COVID-19. Thus, we aimed to explore the effect of risk factors on the severity of the disease, focusing on immune-inflammatory parameters which represent the immune status of patients. Methods A comprehensive systematic search for relevant studies published up to April 2020 was performed by using PubMed, Web of Science, EMBASE, China National Knowledge Internet (CNKI) databases. After extracting all available data of immune-inflammatory indicators, we statistically analyzed the risk factors of severe and nonsevere COVID-19 patients with meta-analysis. Results A total number of 4911 patients from 29 studies were finally included in the meta-analysis. The results demonstrated that severe patients tend to present higher level of white blood cell (WBC), neutrophil, neutrophil-lymphocyte ratio (NLR), procalcitonin (PCT), C-reaction protein (CRP), erythrocyte sedimentation rate (ESR) and Interleukin-6 (IL-6) and decreased number of total lymphocyte and lymphocyte subtypes such as CD4+ T lymphocyte and CD8+ T lymphocyte compared to the nonsevere patients. In addition, WBC count>10ⅹ109/L, lymphocyte count<1ⅹ109/L, PCT>0.5ng/mL, CRP>10 mg/L were risk factors for disease progression in patients with COVID-19 (WBC count>10ⅹ109/L: OR=2.92, 95%CI: 1.96-4.35; lymphocyte count<1ⅹ109/L: OR=4.97, 95%CI: 3.53-6.99; PCT>0.5ng/mL: OR=6.33, 95%CI: 3.97-10.10; CRP>10 mg/L: OR=3.51, 95%CI: 2.38-5.16). Furthermore, we found that NLR, as a novel marker of systemic inflammatory response, can also help predict clinical severity in patients with COVID‐19 (OR=2.50, 95%CI: 2.04-3.06). Conclusions Immune-inflammatory parameters such as WBC, lymphocyte, PCT, CRP and NLR could imply the progression of COVID-19. NLR has taken both the levels of neutrophil and lymphocyte into account, indicating a more complete, accurate and reliable inspection efficiency; surveillance of NLR may help clinicians identify high risk COVID-19 patients at an early stage.